Hope mediates the relationship between depression and quality of life among youths enrolled in a family-based pediatric obesity intervention. Issue 4 (1st October 2016) - Van Allen, Jason; Seegan, Paige L.; Haslam, Aaron; Steele, Ric G.
ABSTRACT: This study examined the hypothesis that hope mediates the relationship between depressive symptoms and health-related quality of life (QOL) among youths with obesity. Children ( N  = 93; aged 7–17) enrolled in the "Positively Fit" treatment study completed the Children's Hope Scale, Behavior Assessment System for Children—Second Edition, Self-Report of Personality Depression Subscale (BASC-2, SRP), and the PedsQL TM to operationalize the hypothesized constructs. A bias corrected bootstrap of the indirect effect was conducted to assess the study hypothesis. There was an indirect effect of depression on QOL through hope. The 95% confidence interval ([CI] = −0.34 to −0.07) had an effect size (standardized indirect effect of −0.14). Hope is a significant mediator of the relationship between depression and QOL. Future research should examine this effect with a longitudinal study design and should test other possible mediators.